2D Salphen-based heteropore covalent organic frameworks for highly efficient electrocatalytic water oxidation. Issue 97 (23rd November 2021) - Wang, Lin-Lin; Zhang, Wen-Da; Li, Tao; Yan, Xiaodong; Gao, Jie; Chen, Yu-Xuan; Shi, Ya-Xiang; Gu, Zhi-Guo
Abstract : A series of 2D covalent organic frameworks with hexagonal and quadrilateral pores were constructed via in situ salphen or metal salphen formation. Abstract : The construction of heteroporous covalent organic frameworks (COFs) is still a challenge. Herein, a series of 2D COFs with hexagonal and quadrilateral pores were constructed via in situ salphen or metal salphen formation. Metallized salphen-based COFs can be used as electrocatalysts towards water oxidation with an overpotential of 266 mV at 10 mA cm −2 .